2021
DOI: 10.3390/ph14080781
|View full text |Cite
|
Sign up to set email alerts
|

Human Hair Keratin Composite Scaffold: Characterisation and Biocompatibility Study on NIH 3T3 Fibroblast Cells

Abstract: The aim of this study was to transform human hair keratin waste into a scaffold for soft tissue engineering to heal wounds. The keratin was extracted using the Shindai method. Keratin and polyvinyl alcohol (PVA) was cross-linked with alginate dialdehyde and converted into a scaffold by the freeze-drying method using gentamycin sulphate (GS) as a model drug. The scaffold was subjected to Fourier transform infrared spectra (FTIR), swelling index, porosity, water absorption, scanning electron microscopy (SEM), di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Free drug in the supernatant liquid was determined by utilizing the UV-spectrophotometer at 245 nm. Methanol was utilized for the necessary dilution process, and the solution was then filtered [ 11 ]. The drug entrapment and loading was calculated from following formula: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free drug in the supernatant liquid was determined by utilizing the UV-spectrophotometer at 245 nm. Methanol was utilized for the necessary dilution process, and the solution was then filtered [ 11 ]. The drug entrapment and loading was calculated from following formula: …”
Section: Methodsmentioning
confidence: 99%
“…In order to investigate the drug release mechanism from nanoparticle formulations, the percentage cumulative drug release data was fitted into mathematical models like first order, Higuchi's model, and the Korsmeyer–Peppas model. The mean results of triplicate measurements and the standard deviation were reported [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The average particle size of ITZ-nPEVs varied from 196.55 ± 0.025 to 252.2 ± 0.019 nm, as reported in Table 1 and Figure S2a. The PDI values of ITZ-nPEVs did not exceed 0.4, indicating that the solution was homogeneous and monodisperse [14]. It was observed that the concentration of lipid increases, the particle size of formulated ITZ-nPEVs also increased.…”
Section: Ps Pdi and Zpmentioning
confidence: 95%
“…The determination of mean particle size, polydispersibility index (PDI), and zeta potential (ZP) of drug and SCs was measured through dynamic dispersion of the light technique using the Zetasizer (Malvern Instruments Ltd., Nano ZS90, Malvern, UK) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%